Access Denied: Enrollment and Retention Challenges for Transgender Students - Dr. Sidra Kiran; Saima Munir; Erum Noreen; Dr. Muhammad Safdar (Research Journal of Psychology, 2025)
The term "transgender" is general. Additionally, to trans men and trans women, it might also contain non-binary individuals. The term "transgender" may be used very broadly to encompass cross-dressers. Other definitions of transgender also include those who belong to a third gender or else conceptualize transgender people as a third gender. The title of the study was " Access Denied: Enrollment and Retention Challenges for Transgender Students." The objective of the study was to identify the specific social, cultural, and institutional barriers that prevented the transgender community from accessing education and to delve into the details of the transgender community members who had successfully navigated these barriers, examining the factors that enabled their success. The research method selected for the study was mixed-method triangulation, chosen in consideration of the nature of the existing status of Pakistan's transgender population, treated as insignificant by mainstream society. A descriptive study design was used. The population of the study consisted of all 1111 transgender individuals in the Rawalpindi area. A non-probability snowball sampling technique was employed, wherein participants assisted the researcher in identifying other similar participants. The sample size for the study consisted of 25% of the population. A self-structured questionnaire was used as a research tool. To obtain detailed information for research purposes, the researcher conducted interviews with the respondents. The content validity of the research tool was established with the guidelines of five different experts in the field of educational research. Their opinions and remarks were used to update the research tool. The reliability of the research tool was determined using Cronbach’s Alpha formula.The researcher personally visited the population area of Rawalpindi, seeking permission for meetings. The researcher also explained the questionnaire to the respondents, and their responses were stored for further analysis. The collected data were used for analysis, conducted using SPSS version 24.The study was significant for the transgender community, society, policymakers, human rights organizations, and the overall education system.